CREATIVE TOURISM AND DESTINATION MARKETING AS A SAFEGUARD OF THE CULTURAL HERITAGE OF REGIONS: THE CASE OF SABUGUEIRO VILLAGE - Sousa, Bruno (2019)
This study entails a reflection on sustainability and specific tourism contexts (i.e. creative tourism). It focusses mainly on local communities’ determiners in the consumer's purchase decision process in creative tourism. This research has as main goal to understand the determiners in the process of the consumer decision in creative tourism contexts, as well as to verify the growing importance of sustainability. A survey was conducted alongside tourists in Portugal (i.e. Sabugueiro village). Twelve qualitative interviews were carried out in Sabugueiro village, as well as direct observation. Besides, an online questionnaire with the intention of collecting the tourist vision about Sabugueiro village was carried out, resulting in forty-one valid answers. Results demonstrated the importance of tourism to Sabugueiro, genuine opinion from the interviwees about negative impacts of turism and about the brand that represents the village. Territorial marketing is a fundamental tool in the promotion of places, one that must be present in the strategies of local government representatives, helping and promoting a sustainable economic and social development of the regions. In addition, the study revealed the view of the tourist about satisfaction with the trip and their sense of responsibility as a tourist for the good development of tourism. It was possible to understand the perception of tourists in Sabugueiro and assess the experience of visitors and the theoretical and practical contributions to local development and public marketing. Implications for future research are also presented